Ultra-smooth carbon film and preparation method and application thereof

By doping metal elements in graphite-like carbon films and combining them with amorphous hydrogen-containing carbon dual spheres, ultraslip carbon films are prepared using unbalanced magnetron sputtering technology, the problem of difficult to achieve macroscopic ultraslip in the prior art is solved, and the friction coefficient is significantly reduced and the high reliability service of mechanical parts is achieved.

CN119571251AActive Publication Date: 2025-03-07TSINGHUA UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411804317.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-07
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a super-slip state on a macroscopic scale, especially in friction and wear scenarios of mechanical parts, and the friction coefficient is difficult to reduce to the order of 0.001.

Method used

A super-slip carbon film is used, and its working layer is a metal-doped graphite-like carbon (GLC) film. It is prepared by unbalanced closed magnetron sputtering technology. The metal doping amount can be adjusted within the range of 0% to 90%, and ultra-slip is achieved with amorphous hydrogen-containing carbon dual spheres.

Benefits of technology

It achieves a super-slip state on the macro scale, and the friction coefficient is reduced to <0.01, which significantly improves the low friction, high stability, long life and high reliability service performance of mechanical parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571251A_ABST
    Figure CN119571251A_ABST
Patent Text Reader

Abstract

The invention relates to a super-smooth carbon film as well as a preparation method and application thereof. The super-smooth carbon film comprises a Cr base layer, a CrC transition layer and a working layer which are sequentially arranged on a substrate, wherein the working layer is a metal-doped GLC thin film; in the working layer, doped metal is selected from metal elements with the characteristic that d electron orbits are not filled, and optionally, the doped metal is any one of Ag, Cu, Ni, Co, Au and the like. The super-smooth carbon film prepared by using a closed field unbalanced magnetron sputtering technology shows good binding force on various substrate materials, metal silver nanoparticles doped in a working layer can be uniformly distributed under a room temperature condition, and the super-smooth carbon film has excellent tribological performance; the super-lubricity carbon films with different metal contents can realize macro-scale super-lubricity in a nitrogen atmosphere, and the friction coefficient is as low as 0.006.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of super-lubricity and friction and wear of mechanical parts, and in particular to a super-lubricity carbon film and a preparation method and application thereof. Background Art

[0002] Tribology has accompanied the origin of human life and the development of society. Nowadays, tribology exists behind almost all super projects. The high precision, high reliability and long service life of mechanical systems are limited by the friction and wear properties of lubricating materials, and many major accidents are caused by friction and wear. Analysis of satellite on-orbit failures shows that among the 272 domestic and foreign satellite failures from 1957 to 2007, 37% of satellite failures were due to lubrication failures of attitude and orbit control subsystems, and more than 50% of attitude and orbit control subsystem failures were caused by wear of space moving parts such as gyroscopes and momentum wheels. For example, in 1986, the Challenger space shuttle failed due to friction failure of the O-ring seal at the right rocket booster connection, resulting in the failure of the fuel tank structure. The space shuttle was torn off layer by layer by violent air friction and disintegrated at the 73rd second of launch; the Galileo spacecraft launched by NASA in 1992 could not transmit signals normally due to high friction, which caused the antenna to not be opened; in 2006, the right front wheel of the Spirit was "arthritic", and the mission failed due to insufficient lubrication. Lubricating materials and technologies are used throughout the entire life cycle of high-end equipment, including mechanical system design, testing, manufacturing, and service. Therefore, low friction, high stability, long life, and high reliability of aerospace moving parts are the key to solving the above problems. Developing new low-friction materials and designing a stable matching system is one of the effective ways to solve the above problems.

[0003] At present, super-lubricity technology is pursuing the ideal state of low friction, that is, achieving a friction coefficient of 0.001. Theoretically, super-lubricity is easy to achieve when the friction interface is free of contaminants, surface defects of the mating pair or saturated dangling bonds, and non-deformed layer-by-layer sliding contact. However, it is difficult to meet the above conditions at the macroscopic scale at the same time, so the large-scale application of super-lubricity is still a major challenge. Summary of the invention

[0004] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of protection of this application.

[0005] The technical problem to be solved by the present application is to provide an ultra-smooth carbon film and a preparation method and application thereof.

[0006] Another technical problem to be solved by the present application is to provide a friction pair super-slip system design including the super-slip carbon film. In the super-slip carbon film described in the present application, the metal doping amount in the working layer of the super-slip carbon film can be adjusted in the range of 0% to 90% in terms of atomic percentage, and can achieve super-slip on a macro scale with the amorphous hydrogen-containing carbon dual sphere pair.

[0007] To solve the above problems, this application provides the following technical solutions: The first aspect of the present application provides an ultra-smooth carbon film, comprising a Cr base layer, a CrC transition layer and a working layer sequentially arranged on a substrate; the working layer is a metal-doped graphite-like carbon (GLC) film, and the GLC film is a hydrogen-free graphite-like carbon film; in the working layer, the doped metal is selected from metal elements having the characteristic of unfilled d electron orbits, optionally, any one of Ag, Cu, Ni, Co, Au, etc.

[0008] In an exemplary embodiment, the sum of the thickness of the Cr base layer and the CrC transition layer is 600-650 nm, and the thickness of the working layer is 900-1600 nm.

[0009] In an exemplary embodiment, in the working layer, the doping amount of the metal is 0% to 90% in atomic percentage, and the doping amount does not include 0%; for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or any two of them as the range between the endpoint values, but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. The "atomic percentage" here means the percentage of the number of atoms of a certain element on the surface of the material to the total number of atoms of all elements.

[0010] In an exemplary embodiment, the doped metal in the working layer is Ag and the doping amount of the metal in the working layer is 18% to 90% in atomic percentage; under this doping condition, a super-slip state can be achieved, and the friction coefficient is less than 0.01.

[0011] In an exemplary embodiment, the doped metal in the working layer is Ag and the doping amount of the metal in the working layer, in terms of atomic percentage, is 18%, 43% or 90%.

[0012] In an exemplary embodiment, the substrate is selected from a silicon wafer or a metal substrate; optionally, the metal substrate is selected from any one of bearing steel, high-temperature alloy, stainless steel, copper, etc.

[0013] The second aspect of the present application provides a method for preparing the above-mentioned ultra-smooth carbon film, which is prepared by using a closed-field four-cathode magnetron sputtering device and an unbalanced closed magnetic field, comprising the following steps: 1) Pretreatment of substrate; 2) Deposition of Cr base layer and CrC transition layer; 3) Deposition of working layer of metal-doped GLC film.

[0014] In an exemplary embodiment, in step 1), the pretreatment of the substrate includes grinding and polishing the substrate, then ultrasonic cleaning the substrate, and then plasma cleaning the substrate.

[0015] In an exemplary embodiment, in step 1), the ultrasonic cleaning step includes: ultrasonically treating the substrate in alcohol and acetone solutions for 15 to 30 min (such as 15 min, 20 min, 25 min, 30 min, etc. or any two of them as range values ​​between endpoint values, but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable), wherein the cleaning times are 2 times with alcohol and 2 times with acetone, and then drying for standby use.

[0016] In an exemplary embodiment, in step 1), the plasma cleaning step includes: placing the cleaned and dried substrate into a coating chamber, and evacuating the vacuum to a degree of less than 1×10 -4 Pa, start ion source cleaning with a current of 1 ~ 2 A. In an argon atmosphere, bombard the substrate with high-energy plasma at an operating voltage of 400 ~ 500 V (such as 400 V, 450 V, 500 V, etc. or any two values ​​thereof as the range value between the endpoint values, but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable), and a gas pressure of 2 ~ 3 Pa for 20 ~ 30 min (such as 20 min, 25 min, 30 min, etc. or any two values ​​thereof as the range value between the endpoint values, but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable).

[0017] In an exemplary embodiment, in the plasma cleaning of step 1), the current is 1.5 A and the gas pressure is 2.5 Pa.

[0018] In an exemplary embodiment, in step 2), the step of depositing a Cr base layer and a CrC transition layer includes: maintaining an ion source current of 1 to 2 A and controlling the gas pressure at 2 to 3 Pa; turning on a chromium target to first deposit a Cr base layer, with a current of 6.0 to 7.5 A (such as 6.0 A, 6.5 A, 7.0 A, 7.5 A, etc. or any two of them as a range value between the endpoint values, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable), and a deposition time of 25 to 35 min; then turning on a carbon target and a chromium target at the same time to prepare a CrC transition layer, with a chromium target current of 6.0 to 7.5 A and a carbon target current of 1.0 to 2.5 A (such as 1.0 A, 1.5 A, 2.0 A, 2.5 A, etc. or any two of them as a range value between the endpoint values, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable), and a deposition time of 25 to 35 min, and during the deposition process, the working voltages of the chromium target and the carbon target are both controlled at 300 to 400 V. 500 V (such as 300 V, 350 V, 400 V, 450 V, 500 V, etc. or a range between any two of them as endpoint values, but not limited to the listed values, other unlisted values ​​within the range are also applicable).

[0019] In an exemplary embodiment, in step 2), the ion source current is maintained at 1.5 A, the gas pressure is maintained at 2.5 Pa, the deposition time of the Cr base layer is 30 min, and the deposition time of the CrC transition layer is 30 min.

[0020] In an exemplary embodiment, in step 3), the working layer is obtained by co-sputtering a metal target and a carbon target, comprising the following steps: controlling the ion source current to 2 to 3 A, the working voltage to 50 to 70 V, and keeping the gas pressure unchanged; turning on the metal target and the carbon target at the same time, the carbon target working voltage is 400 to 450 V (such as 400 V, 410 V, 420 V, 430 V, 440 V, 450 V, etc. or any two of them as the range value between the endpoint values, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable), the carbon target working current is 7.0 to 8.0 A (such as 7.0 A, 7.5 A, 8.0 A, etc. or any two of them as the range value between the endpoint values, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable); the metal target working voltage is 300 to 450 V (such as 300 V, 350 V, 400 V, 450 V V, etc. or any two of them as the range values ​​between the endpoint values, but not limited to the listed values, other values ​​not listed in the numerical range are also applicable), the working current of the metal target is 0 ~ 1.2 A, excluding 0 A, to control the amount of metal doping in the carbon-based film; keeping other gas pressure conditions unchanged, the deposition is 6 ~ 8 h ((such as 6 h, 6.5 h, 7 h, 7.5 h, 8 h, etc. or any two of them as the range values ​​between the endpoint values, but not limited to the listed values, other values ​​not listed in the numerical range are also applicable), to obtain GLC films with different metal doping amounts.

[0021] In an exemplary embodiment, in step 3), the ion source current is controlled to be 2.5 A, the operating voltage is controlled to be 60 V, and the gas pressure is controlled to be 2.5 Pa.

[0022] In an exemplary embodiment, the method comprises the following steps: 1) Using silicon wafer as deposition substrate, ultrasonic treatment was performed in alcohol and acetone solution for 15 min respectively, wherein the cleaning times were 2 times with alcohol and 2 times with acetone, and then drying was performed for later use; 2) Place the cleaned and dried substrate sample into the coating chamber and evacuate the vacuum to less than 1×10 -4 Pa, start ion source cleaning, the current is 1.5 A, and bombard the substrate with high-energy plasma in an argon atmosphere, the working voltage is 430 V, and the pressure is 2.5 Pa for 25 min; 3) Deposition of Cr base layer and CrC transition layer: Keep the ion source current at 1.5 A and the gas pressure at 2.5 Pa, turn on the chromium target to first deposit the Cr base layer, the current is 7.5 A, and the deposition time is 30 min; then turn on the carbon target and chromium target at the same time to prepare the CrC transition layer, the chromium target current is 7.5 A, the carbon target current is 2.5 A, and the deposition time is 30 min. During the entire deposition process, the working voltage of the chromium target and the carbon target are controlled at 400 V; 4) Deposition of the working layer of the silver-doped GLC film: control the ion source current to 2.5 A and the working voltage to 60 V; turn on the silver target and the carbon target at the same time, the carbon target working voltage is 420 V and the current is 7.5 A; the silver target voltage is 410 V and the working current is 0.20 A; keep other gas pressure conditions unchanged and deposit for 7 h to obtain a GLC film with a silver content of 18%.

[0023] In an exemplary embodiment, the method comprises the following steps: 1) Using silicon wafer as deposition substrate, ultrasonic treatment was performed in alcohol and acetone solution for 15 min respectively, wherein the cleaning times were 2 times with alcohol and 2 times with acetone, and then drying was performed for later use; 2) Place the cleaned and dried substrate sample into the coating chamber and evacuate the vacuum to less than 1×10 -4 Pa, start ion source cleaning, the current is 1.5 A, and bombard the substrate with high-energy plasma in an argon atmosphere. The working voltage is 480 V and the pressure is 2.5 Pa for 25 min; 3) Deposition of Cr base layer and CrC transition layer: Keep the ion source current at 1.5 A and the gas pressure at 2.5 Pa, turn on the chromium target to first deposit the Cr base layer, the current is 7.0 A, and the deposition time is 30 min; then turn on the carbon target and chromium target at the same time to prepare the CrC transition layer, the chromium target current is 7.0 A, the carbon target current is 2.5 A, and the deposition time is 30 min. During the entire deposition process, the working voltages of the chromium target and the carbon target are controlled at 350 V; 4) Deposition of the working layer of the silver-doped GLC film: control the ion source current to 2.5 A and the working voltage to 60 V; turn on the silver target and the carbon target at the same time, the carbon target working voltage is 400 V and the current is 8.0 A; the silver target voltage is 380 V and the working current is 0.55 A; keep other gas pressure conditions unchanged and deposit for 6 h to obtain a GLC film with a silver content of 43%.

[0024] In an exemplary embodiment, the method comprises the following steps: 1) Using silicon wafer as deposition substrate, ultrasonic treatment was performed in alcohol and acetone solution for 15 min respectively, wherein the cleaning times were 2 times with alcohol and 2 times with acetone, and then drying was performed for later use; 2) Place the cleaned and dried substrate sample into the coating chamber and evacuate the vacuum to less than 1×10 -4 Pa, start ion source cleaning, the current is 1.5 A, and bombard the substrate with high-energy plasma in an argon atmosphere, the working voltage is 500 V, and the pressure is 2.5 Pa for 20 min; 3) Deposition of Cr base layer and CrC transition layer: Keep the ion source current at 1.5 A and the gas pressure at 2.5 Pa, turn on the chromium target to first deposit the Cr base layer, the current is 7.5 A, and the deposition time is 30 min; then turn on the carbon target and chromium target at the same time to prepare the CrC transition layer, the chromium target current is 7.5 A, the carbon target current is 2.0 A, and the deposition time is 30 min. During the entire deposition process, the working voltage of the chromium target and the carbon target are controlled at 500 V; 4) Deposition of the working layer of the silver-doped GLC film: control the ion source current to 2.5 A and the working voltage to 60 V; turn on the silver target and the carbon target at the same time, the carbon target working voltage is 450 V and the current is 8.0 A; the silver target voltage is 450 V and the working current is 1.20 A; keep other gas pressure conditions unchanged and deposit for 8 h to obtain a GLC film with a silver content of 90%.

[0025] The third aspect of the present application provides an ultra-smooth carbon film prepared by the above method.

[0026] The fourth aspect of the present application provides a method for achieving super-slippery properties using the above-mentioned super-slippery carbon film.

[0027] In an exemplary embodiment, the method includes forming a friction pair of dual balls of the super-lubricant carbon film and amorphous hydrogen-containing carbon film to achieve super-lubricity in a nitrogen atmosphere.

[0028] In an exemplary embodiment, the amorphous hydrogenated carbon film dual ball refers to a Φ6 mm steel ball coated with an amorphous hydrogenated carbon film.

[0029] Compared with the prior art, this application has the following advantages: 1. The present application modulates the target GLC film by unbalanced magnetron sputtering, and the process parameters are designed so that the metal nanoparticles have good dispersion and uniformity in the amorphous carbon network.

[0030] 2. The present application designs suitable tooling during the process of preparing the thin film, which can achieve conformal plating while ensuring uniform and high-bonding preparation of the working layer film.

[0031] 3. The present application arbitrarily selects the doping metal from metal elements having the characteristic of unfilled d electron orbitals.

[0032] 4. The metal-doped GLC film prepared in the present application exhibits an excellent robust superlubricity, especially the tribological performance of the silver-doped graphite-like superlubricious carbon film and the amorphous hydrogen-containing carbon film dual ball was tested in an Anton Paar friction tester. The results showed that the silver nanoparticles dispersed in the amorphous carbon network can induce the surrounding amorphous carbon network to graphitize and tend to order under the induction of friction during the friction process, generating a graphene-like structure. The hydrogen-containing carbon film on the dual ball can synergistically reduce the interfacial shear force. Under the joint action of the silver-doped GLC film and the amorphous hydrogen-containing carbon dual ball, the superlubricity range of the carbon film on the macroscopic scale is broadened and the friction coefficient is further reduced (friction coefficient <0.01).

[0033] Other features and advantages of the present application will be described in the following description, or understood by practicing the present application. Other advantages of the present application can be realized and obtained by the solutions described in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.

[0035] Figure 1 This is a schematic diagram of the structure of the ultra-smooth carbon film prepared in this application, wherein 1 is the substrate, 2 is the Cr base layer, 3 is the CrC transition layer, and 4 is the working layer.

[0036] Figure 2 The friction coefficient curve obtained for the super-slippery carbon film and the amorphous hydrogen-containing dual sphere constructed in this application. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present application more clear, the embodiments of the present application will be described in detail below. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other arbitrarily without conflict.

[0038] The present application is further described in detail below in conjunction with specific embodiments, but the embodiments should not be construed as limiting the present application.

[0039]

Tribological performance testing

[0040] Example 1 like Figure 1 As shown, a super-smooth carbon film is prepared by sputtering a silver target. The film refers to a silver-doped GLC film deposited on the surface of a silicon substrate with a silver target sputtering current of 0.2 A, and the silver content is 18% in atomic percentage.

[0041] The method for preparing the ultra-smooth carbon film comprises the following steps: (1) Using a silicon wafer as a deposition substrate, ultrasonically treat it in an alcohol solution and an acetone solution for 15 min, respectively. The cleaning times are 2 times with alcohol and 2 times with acetone, and then dry it for later use; (2) Place the cleaned and dried substrate sample into the coating chamber and evacuate the vacuum to less than 1×10 -4 Pa, start ion source cleaning, the current is 1.5 A, and bombard the substrate with high-energy plasma in an argon atmosphere, the working voltage is 430 V, and the pressure is 2.5 Pa for 25 min; (3) Deposition of Cr base layer and CrC transition layer: Keep the ion source current at 1.5 A and the gas pressure at 2.5 Pa. Turn on the chromium target to first deposit the Cr base layer. The current is 7.5 A and the deposition time is 30 min. Then turn on the carbon target and chromium target at the same time to prepare the CrC transition layer. The chromium target current is 7.5 A, the carbon target current is 2.5 A, and the deposition time is 30 min. During the entire deposition process, the working voltage of the chromium target and the carbon target are controlled at 400 V. (4) Deposition of silver-doped GLC thin film working layer: control the ion source current to 2.5 A and the working voltage to 60 V; turn on the silver target and carbon target at the same time, the carbon target working voltage is 420 V and the current is 7.5 A; the silver target voltage is 410 V and the working current is 0.20 A; keep other gas pressure conditions unchanged and deposit for 7 h to obtain a GLC film with a silver content of 18%.

[0042] The friction pair system of the super-slip carbon film: The super-slippery carbon film prepared above was paired with a 6 mm diameter amorphous hydrogenated carbon film dual ball. The friction test was carried out using an Anton Paar friction and wear tester under load of 5 N, frequency of 5 Hz, amplitude of 5 mm, nitrogen atmosphere, and room temperature for 15 min. The friction pair was placed in a dry nitrogen environment by repeatedly filling and discharging nitrogen in the cavity, and a curve of the friction coefficient changing with time was obtained. The results show that when the silver content is 18%, the friction coefficient of the system is 0.006, achieving macroscopic super-slip (see for details). Figure 2 ).

[0043] Example 2 like Figure 1 As shown, a super-smooth carbon film is prepared by sputtering a silver target. The film refers to a silver-doped GLC film deposited on the surface of a silicon substrate with a silver target sputtering current of 0.55 A, and the silver content is 43% in atomic percentage.

[0044] The method for preparing the ultra-smooth carbon film comprises the following steps: (1) Using a silicon wafer as a deposition substrate, ultrasonically treat it in an alcohol solution and an acetone solution for 15 min, respectively. The cleaning times are 2 times with alcohol and 2 times with acetone, and then dry it for later use; (2) Place the cleaned and dried substrate sample into the coating chamber and evacuate the vacuum to less than 1×10 -4 Pa, start ion source cleaning, the current is 1.5 A, and bombard the substrate with high-energy plasma in an argon atmosphere. The working voltage is 480 V and the pressure is 2.5 Pa for 25 min; (3) Deposition of Cr base layer and CrC transition layer: Keep the ion source current at 1.5 A and the gas pressure at 2.5 Pa. Turn on the chromium target to first deposit the Cr base layer. The current is 7.0 A and the deposition time is 30 min. Then turn on the carbon target and chromium target at the same time to prepare the CrC transition layer. The chromium target current is 7.0 A, the carbon target current is 2.5 A, and the deposition time is 30 min. During the entire deposition process, the working voltage of the chromium target and the carbon target are controlled at 350 V. (4) Deposition of the working layer of the silver-doped GLC film: control the ion source current to 2.5 A and the working voltage to 60 V; turn on the silver target and the carbon target at the same time, the carbon target working voltage is 400 V and the current is 8.0 A; the silver target voltage is 380 V and the working current is 0.55 A; keep other gas pressure conditions unchanged and deposit for 6 h to obtain a GLC film with a silver content of 43%.

[0045] The friction pair system of the super-slip carbon film: The prepared super-slippery carbon film was paired with a 6 mm diameter amorphous hydrogenated carbon film dual ball. The friction test was carried out using an Anton Paar friction and wear tester under the conditions of load 3 N, frequency 5 Hz, amplitude 5 mm, nitrogen atmosphere, and room temperature for 10 min. The friction pair was placed in a dry nitrogen environment by repeatedly filling and discharging nitrogen in the cavity, and the friction coefficient change curve over time was obtained. The results show that when the silver content is 43%, the friction coefficient of the system is 0.007, achieving macroscopic super-slip (see for details). Figure 2 ).

[0046] Example 3 like Figure 1 As shown, a super-smooth carbon film is prepared by sputtering a silver target. The film refers to a silver-doped GLC film deposited on the surface of a silicon substrate with a silver target sputtering current of 1.2 A, and the silver content is 90% in atomic percentage.

[0047] The method for preparing the ultra-smooth carbon film comprises the following steps: (1) Using a silicon wafer as a deposition substrate, ultrasonically treat it in an alcohol solution and an acetone solution for 15 min, respectively. The cleaning times are 2 times with alcohol and 2 times with acetone, and then dry it for later use; (2) Place the cleaned and dried substrate sample into the coating chamber and evacuate the vacuum to less than 1×10 -4 Pa, start ion source cleaning, the current is 1.5 A, and bombard the substrate with high-energy plasma in an argon atmosphere, the working voltage is 500 V, and the pressure is 2.5 Pa for 20 min; (3) Deposition of Cr base layer and CrC transition layer: Keep the ion source current at 1.5 A and the gas pressure at 2.5 Pa. Turn on the chromium target to first deposit the Cr base layer. The current is 7.5 A and the deposition time is 30 min. Then turn on the carbon target and chromium target at the same time to prepare the CrC transition layer. The chromium target current is 7.5 A and the carbon target current is 2.0 A. The deposition time is 30 min. During the entire deposition process, the working voltage of the chromium target and the carbon target are controlled at 500 V. (4) Deposition of the working layer of the silver-doped GLC film: control the ion source current to 2.5 A and the working voltage to 60 V; turn on the silver target and the carbon target at the same time, the carbon target working voltage is 450 V and the current is 8.0 A; the silver target voltage is 450 V and the working current is 1.20 A; keep other gas pressure conditions unchanged and deposit for 8 h to obtain a GLC film with a silver content of 90%.

[0048] The friction pair system of the super-slip carbon film: The prepared super-slippery carbon film and the amorphous hydrogenated carbon film dual ball with a diameter of 6 mm were used to form a friction pair. The friction test was carried out using an Anton Paar friction and wear tester under the conditions of a load of 3 N, a frequency of 5 Hz, an amplitude of 5 mm, and a nitrogen atmosphere at room temperature for 15 min. The friction pair was placed in a dry nitrogen environment by repeatedly filling and discharging nitrogen in the cavity, and a curve of the friction coefficient changing with time was obtained. The results show that when the silver content is 90%, the system has a longer running-in period. Subsequently, the conditions were kept unchanged, and the friction experiment was continued on the above-mentioned wear mark for 6 min. The friction coefficient was reduced to 0.009, achieving super-slip on a macro scale (see for details). Figure 2 ).

[0049] In the above-mentioned embodiments 1 to 3, the silver (Ag)-doped nanoparticles may be replaced by other metal elements having the characteristic of unfilled d electron orbits, such as Cu, Ni, Co, Au, etc.

[0050] Comparative Example 1 A super-smooth carbon film is prepared by sputtering a silver target. The film refers to a silver-doped GLC film deposited on a silicon substrate surface with a silver target sputtering current of 0 A, and the silver content is 0%, that is, when there is no metal element doping in the GLC film.

[0051] The method for preparing the ultra-smooth carbon film comprises the following steps: (1) Using a stainless steel sheet as a deposition substrate, ultrasonically treat it in an alcohol solution and an acetone solution for 30 min, respectively. The cleaning times are 2 times with alcohol and 2 times with acetone, and then dry it for later use. (2) Place the cleaned and dried substrate sample into the coating chamber and evacuate the vacuum to less than 1×10 -4 Pa, start ion source cleaning, the current is 1.5 A, and bombard the substrate with high-energy plasma in an argon atmosphere, the working voltage is 400 V, and the pressure is 2.5 Pa for 30 min; (3) Deposition of Cr base layer and CrC transition layer: Keep the ion source current at 1.5 A and the gas pressure at 2.5 Pa. Turn on the chromium target to first deposit the Cr base layer. The current is 6.0 A and the deposition time is 30 min. Then turn on the carbon target and chromium target at the same time to prepare the CrC transition layer. The chromium target current is 6.0 A, the carbon target current is 1.0 A, and the deposition time is 30 min. During the entire deposition process, the working voltage of the chromium target and the carbon target are controlled at 300 V. (4) Deposition of GLC thin film working layer: Control the ion source current to 2.5 A and the working voltage to 60 V; only turn on the carbon target, the carbon target working voltage is 400 V, and the current is 7.0 A. Keep other gas pressure conditions unchanged and deposit for 6 h to obtain a GLC film with a silver content of 0%.

[0052] The friction pair system of the super-slip carbon film: The prepared super-slippery carbon film was paired with an amorphous hydrogenated carbon film with a diameter of 6 mm. The friction test was carried out using an Anton Paar friction and wear tester under the conditions of load 3 N, frequency 5 Hz, amplitude 5 mm, nitrogen atmosphere, and room temperature for 15 min. The friction pair was placed in a dry nitrogen environment by repeatedly filling and discharging nitrogen in the cavity, and the friction coefficient curve over time was obtained. The results show that when the silver content is 0%, the system cannot achieve super-slippery.

[0053] The above embodiments and comparative examples show that super-slippery cannot be achieved on a macroscopic scale when no metal elements are doped in the carbon-based film; when metal elements with the characteristic of unfilled d orbitals, such as silver, are doped into the GLC working layer, robust super-slippery can be achieved on a macroscopic scale, that is, a super-slippery carbon film is successfully obtained by the method provided in the present application and super-slippery applications can be realized.

[0054] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A super-smooth carbon film, characterized in that: The ultra-smooth carbon film comprises a Cr base layer, a CrC transition layer and a working layer which are sequentially arranged on a substrate; wherein the working layer is a metal-doped GLC film; in the working layer, the doped metal is selected from metal elements having the characteristic of unfilled d electron orbits, optionally any one of Ag, Cu, Ni, Co and Au.

2. The ultra-smooth carbon film according to claim 1, characterized in that: The sum of the thickness of the Cr base layer and the CrC transition layer is 600-650 nm, and the thickness of the working layer is 900-1600 nm.

3. The ultra-smooth carbon film according to claim 2, characterized in that: In the working layer, the metal doping amount is 0% to 90% in atomic percentage, and the doping amount does not include 0%.

4. The ultra-smooth carbon film according to any one of claims 1 to 3, characterized in that: In the working layer, the doped metal is Ag and in the working layer, the doping amount of the metal is 18% to 90% in atomic percentage.

5. A method for preparing an ultra-smooth carbon film according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Pretreatment of the substrate, including grinding and polishing the substrate, then ultrasonic cleaning, and then plasma cleaning the substrate; the substrate is selected from a silicon wafer or a metal substrate; optionally, the metal substrate is selected from any one of bearing steel, high-temperature alloy, stainless steel, and copper; 2) Depositing a Cr base layer and a CrC transition layer, including: maintaining an ion source current of 1 to 2 A, controlling the gas pressure at 2 to 3 Pa, turning on a chromium target to first deposit a Cr base layer, the current being 6.0 to 7.5 A, and the deposition time being 25 to 35 min; then simultaneously turning on a carbon target and a chromium target to prepare a CrC transition layer, the chromium target current being 6.0 to 7.5 A, the carbon target current being 1.0 to 2.5 A, and the deposition time being 25 to 35 min, and during the entire deposition process, the operating voltages of the chromium target and the carbon target are both controlled at 300 to 500 V; 3) Depositing a metal-doped GLC thin film working layer, wherein the working layer is obtained by co-sputtering a metal target and a carbon target, including: controlling the ion source current to 2 to 3 A, the working voltage to 50 to 70 V, turning on the metal target and the carbon target at the same time, the carbon target working voltage to 400 to 450 V, and the carbon target working current to 7.0 to 8.0 A; the metal target working voltage to 300 to 450 V, and the metal target working current to 0 to 1.2 A, excluding 0 A; keeping other gas pressure conditions unchanged, depositing for 6 to 8 h, and obtaining GLC films doped with different metal contents.

6. The method according to claim 5, characterized in that In step 1), the ultrasonic cleaning step comprises: ultrasonically treating the substrate in alcohol and acetone solutions for 15 to 30 minutes respectively; wherein the cleaning times are 2 times with alcohol and 2 times with acetone, and then drying for standby use; The plasma cleaning step includes: placing the cleaned and dried substrate into a coating chamber, and evacuating the vacuum to a degree of less than 1×10 -4 Pa, turn on the ion source for cleaning, the current is 1 ~ 2 A, and the substrate is bombarded with high-energy plasma in an argon atmosphere. The working voltage is 400 ~ 500 V and the gas pressure is 2 ~ 3 Pa for 20 ~ 30 min.

7. The method according to claim 6, characterized in that In the plasma cleaning of step 1), the current is 1.5 A and the gas pressure is 2.5 Pa.

8. The method according to any one of claims 5 to 7, characterized in that In step 2), the ion source current was maintained at 1.5 A, the gas pressure was maintained at 2.5 Pa, the deposition time of the Cr base layer was 30 min, and the deposition time of the CrC transition layer was 30 min; In step 3), the ion source current was controlled to be 2.5 A, the operating voltage to be 60 V, and the gas pressure to be 2.5 Pa.

9. An ultra-smooth carbon film prepared by the method according to any one of claims 5 to 8.

10. A method for achieving super-slippery carbon film using any one of claims 1 to 4 and 9, characterized in that: The method comprises forming a friction pair of dual balls of the super-slippery carbon film and amorphous hydrogen-containing carbon film to achieve super-slippery in a nitrogen atmosphere.

Citation Information

Patent Citations

  • Silver-doped graphite-like carbon coating and preparation method thereof

    CN107881466A

  • Super-lubricity performance metal / hydrogen-containing carbon composite thin film and preparation method thereof

    CN111850470A

  • Stainless steel-based fuel cell bipolar plate surface composite coating and preparation method thereof

    CN112609165A

  • Silver and copper doped graphite nano multilayer film and preparation method thereof

    CN116657087A

  • GLC coating and preparation method thereof

    CN117127147A